(untitled) (Research, Society and Development, 2022)
This study aimed to review the scientific literature on musculoskeletal pain and ergonomics in times of home office. Complete scientific documents in Portuguese and English, not duplicated, published in the years 2020 and 2021 were consulted in the Google Scholar, Virtual Health Library (BVS) and PubMed databases, with the descriptors "Musculoskeletal Pain", "Ergonomics", “Home Office” and “COVID-19”, using the Boolean operator “AND”. The documents selected for this research were analyzed from an integrative review. 613 scientific documents were identified, 10 of which make up the corpus of this review. As the main finding, it was identified that there was the emergence or increase of musculoskeletal pain during the home office period, and the body regions most affected by musculoskeletal pain are the cervical spine, lumbar spine, shoulders and knees. It is expected that the results presented can contribute to the elaboration of public policies and actions to face these diseases.